The Importance of the Role of the Young Generation in Improving Agricultural Quality at Kp. Leuwinutug Rt 02/06 - Dina Rosita; Endah Robiatul Adawiah; Arisal Sopyan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The role of youth in improving the quality of agriculture is very important, the results of the research that I have done are that there is still little interest from the younger generation in improving the quality of agriculture in kp.leuwinutug, the author's goal in making this journal is to motivate young people, especially the youth in kp.leuwinutug. The method used is a qualitative method, namely by directly examining the situation in the field where we can see directly the conditions that occur in the world of agriculture. The agricultural sector is a sector that has a strategic role in the structure of national economic development. Sustainable agricultural development requires the role of quality human resources and strong commitment in the development of the agricultural sector. These two things will later become the basis for the success of sustainable agricultural development. This sector is a sector that does not receive serious attention from the government in nation building. However, this sector is a sector that accommodates a large number of workers and most of our population depends on it.